Analisis Hukum Terhadap Putusan Hakim Pengadilan Tinggi Sumatera Barat Nomor 8/PID/2018/PT.PDG Dikaitkan dengan Tujuan Pemidanaan - Arfendi, Jefri; Firdaus, Emilda; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Judges who decide to consider, seek justice come to ask for justice, if they do not find a written law, they must collect unwritten laws to decide based on the law as those who argue and are responsible. In decision number 8/PID/2018/PT.PDG the panel of judges handed down the verdict that the defendant was placed under house arrest. With the verdict of the panel of judges who sentenced the defendant to prison, the purpose of a conviction was not fulfilled.This type of research can be classified in the type of normative legal research, an attempt to find whether the applied law is suitable for solving a particular case or problem, where the sound of the rules is found. Based on the nature of this legal research, it is descriptive in nature, namely reviewing the subject matter in accordance with the scope and identification of the problem through a law approach carried out by examining the laws and regulations relating to the legal issues being studied.From the results of research and discussion it can be concluded that, First, the Judge's Consideration in Imposing Criminal Sanctions Against Frauders in Decision Number 8/PID/2018/PT.PDG is the defendant fulfilling the elements of criminal acts as regulated in Article 378 of the Criminal Code. Reasons that incriminate the criminal: while carrying out their actions the Defendant is still a civil servant in the Padang High Prosecutor's Office and the Defendant's actions have dishonored the Attorney's institution as a law enforcement institution. As well as circumstances that alleviate criminality: The defendant still has children who are still breastfeeding. Second, the legal analysis of verdict number 8/PID/2018/PT.PDG is starting from the indictment which mixes a series of acts between fraud and embezzlement, not the maximum demands given by the public prosecutor, then the judge in determining the crime as if too much guided by the demands of the public prosecutor, without regard to the facts of the trial which incriminated many defendants.Keywords: Decision - Judge Considerations - Criminal Purpose.